Enhanced brain delivery and therapeutic activity of trastuzumab after blood-brain barrier opening by NEO100 in mouse models of brain-metastatic breast cancer. Issue 10 (28th February 2021) - Wang, Weijun; He, Haiping; Marín-Ramos, Nagore I; Zeng, Shan; Swenson, Steven D; Cho, Hee-Yeon; Fu, Jie; Beringer, Paul M; Neman, Josh; Chen, Ligang; Schönthal, Axel H; Chen, Thomas C
Abstract: Background: The antitumor efficacy of human epidermal growth factor receptor 2 (HER2)-targeted therapies, such as humanized monoclonal antibody trastuzumab (Herceptin ®, Roche), in patients with breast-to-brain cancer metastasis is hindered by the low permeability of the blood-brain barrier (BBB). NEO100 is a high-purity version of the natural monoterpene perillyl alcohol, produced under current good manufacturing practice (cGMP) regulations, that was shown previously to reversibly open the BBB in rodent models. Here we investigated whether NEO100 could enable brain entry of trastuzumab to achieve greater therapeutic activity. Methods: An in vitro BBB, consisting of human astrocytes and brain endothelial cells, was used to determine trastuzumab penetration in the presence or absence of NEO100. For in vivo studies, we administered intravenous (IV) trastuzumab or the trastuzumab-drug conjugate ado-trastuzumab emtansine (T-DM1; Kadcyla ®, Roche), to mouse models harboring intracranial HER2+ breast cancer, with or without BBB opening via IA NEO100. Brain and tumor tissues were examined for the presence of trastuzumab and infiltration of immune cells. Therapeutic impact was evaluated based on overall survival. Results: NEO100 greatly increased trastuzumab penetration across an in vitro BBB. In vivo, IA NEO100-mediated BBB opening resulted in brain tumor-selective accumulation of trastuzumab, without detectable presence in normal brain tissue, along with increased presence of immune cell populations. IV delivery of trastuzumab or T-DM1 achieved significantly greater overall survival of tumor-bearing mice when combined with IA NEO100. Conclusion: IA NEO100 facilitates brain tumor entry of trastuzumab and T-DM1 and significantly enhances their therapeutic efficacy, along with increased antibody-dependent immune cell recruitment.